The Department Chair New Roles, Responsibilities and Challenges. ASHE-ERIC Higher Education Report No. 1 - Seagren, Alan T.; Association for the Study of Higher Education; ERIC Clearinghouse on Higher Education; George Washington Univ., Washington, DC. School of Education and Human Development (Washington, DC : ERIC Clearinghouse on Higher Education, 1993)
This monograph explores the changing role of the academic department chair in the areas of leadership, influence, and faculty development. The paper uses research insights to explore the situation of an academic chair who is squeezed between the demands of upper administration and the expectations of faculty, staff, and students. Studies of the roles and responsibilities of chairs consistently show that the role is ambiguous, unclear in authority, and difficult to classify as faculty or administrator. The tradition of faculty ownership dictates that chair leadership must emphasize empowering activities. The most effective use of political influence and power understands the political forces and processes of the institution and maneuvers groups and coalitions to achieve the autonomy and control necessary to a strong department. Faculty evaluation provides a chair with a powerful opportunity for developing quality. In addition, the chair must recognize how institutional type, history, and culture, model of governance, and discipline can influence what is expected. In the coming years chairs will need a program of professional development on many fronts to acquire the skills to address the complex challenges they will face. (Contains over 200 references.) (JB)
Availability: ASHE-ERIC Higher Education Reports, The George Washington University, One Dupont Circle, Suite 630, Washington, DC 20036-1183 (
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RI88062014.
ERIC Note: For the digest, see HE 026 771.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Characteristics; Administrator Responsibility; Administrator Role; College Administration; Department Heads; Faculty Evaluation; Higher Education; Institutional Characteristics; Leadership; Political Power; Professional Development; Teacher Administrator Relationship; ERIC Publications